Da Subsunção real dos indivíduos no seu tempo livre pela atual vanguarda da indústria cultural - Lucas Alves Marinho (2022)
This work proposes a reassessment of the economic and ideological determinations of classical Adornian theorization, regarding the Cultural Industry. And, seeking to be faithfull to the historicity of the phenomenon, as Adorno was, it critically resumes and updates the critical potential of these classical determinations, in dialogue with some other important references. Demonstrating that, in its current avant-garde configuration (i. e., in mobile social media), the cultural industry, in addition to spreadind, reaching nooks of privacy and spare time previously unimaginable, qualitatively modified its determinations, estabilishing another way of relationship with its typical consumers – another way that, compared to those of the classical media analyzed by Adorno, finally performs the subsumption of individuals placed under the ubiquitous influence of the cultural industry during their spare time. Another mode of relationship that was historically established insofar as the cultural industry: appropriated leisure activities traditionally carried out according to its own, natural- spontaneous temporality; it segmented them and projected them onto the homogeneous flow, technically objectified by its machinery.